Un concepto no covencional basado en "flutter" para cosechar energía - Pérez Segura, Martín Eduardo (2020)
Energy harvesting has currently taken a central role due to its application to feed low power devices, such as wireless sensors, radio-frequency transceivers, charging devices and cameras. Among other alternatives, wind energy harvesting based on aeroelastic phenomena plays a pivotal role in providing sufficient power for extended operation of such devices with little or no battery replacement. In this article, a concept that explores the possibility of harvesting wind energy using an array of harvesting devices is presented. Each device is built as a long span multifunctionalwing that exhibits oscillatory motions under the action of the wind. The efficiency of these systems depends on inherently non-linear phenomena, as well as on the aerodynamic synergy between the harvesters, and between them and their wakes. In addition, a preliminary study of the feasibility of the concept is conducted through cosimulation techniques that allow one to investigate the fluid-structure interaction. The results of this effort are encouraging since they highlight the potential not only of the proposed concept but also of the combination of these new technologies with aeroelastic analysis and design methods to create a new generation of power harvesters.